2012
DOI: 10.1088/0004-637x/745/2/172
|View full text |Cite
|
Sign up to set email alerts
|

SPITZERMID-IR SPECTROSCOPY OF POWERFUL 2 JY AND 3CRR RADIO GALAXIES. I. EVIDENCE AGAINST A STRONG STARBURST-AGN CONNECTION IN RADIO-LOUD AGN

Abstract: We present deep Spitzer/IRS spectra for complete samples of 46 2Jy radio galaxies (0.05 Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
136
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 90 publications
(152 citation statements)
references
References 79 publications
13
136
3
Order By: Relevance
“…Second, our result that many small radio sources are hosted by strongly star-forming galaxies is consistent with the observational/theoretical finding that radio jets may induce bursts of star formation (positive feedback, e.g. Silk 2013) in the hosts of high-z (Dey et al 1997;van Breugel et al 1998) and low-z radio-loud AGN (Tadhunter et al 2011;Dicken et al 2012). Best et al (1996) found that smaller radio sources show stronger alignment effect 5 providing further support for the incidence of positive feedback in hosts of small radio sources.…”
Section: Subgalactic Versus Supergalactic Radio Sourcessupporting
confidence: 90%
“…Second, our result that many small radio sources are hosted by strongly star-forming galaxies is consistent with the observational/theoretical finding that radio jets may induce bursts of star formation (positive feedback, e.g. Silk 2013) in the hosts of high-z (Dey et al 1997;van Breugel et al 1998) and low-z radio-loud AGN (Tadhunter et al 2011;Dicken et al 2012). Best et al (1996) found that smaller radio sources show stronger alignment effect 5 providing further support for the incidence of positive feedback in hosts of small radio sources.…”
Section: Subgalactic Versus Supergalactic Radio Sourcessupporting
confidence: 90%
“…Seymour et al 2011;Dicken et al 2012;Magliocchetti et al 2014;Podigachoski et al 2015;Magliocchetti et al 2016). It also confirms and extends the high star-forming activity observed in the hosts of radio-active AGN selected by different methods (e.g.…”
Section: Star Formation In Rg and Rlqsupporting
confidence: 79%
“…Most of these sources are bright compact radio sources, with sizes ranging from 0.01 to 40 kpc. These H i-outflow objects appear to belong to the minority of powerful radio galaxies (≈35%) that show evidence for recent star formation at optical wavelengths , based on spectral synthesis modeling) and/or mid-IR wavelengths (Dicken et al 2012, based on PAH detection). Most such objects are compact radio sources (e.g., CSS/GPS/CSO) or have unusually strong compact steep spectrum cores .…”
Section: The Sample Of H I-outflow Radio Galaxiesmentioning
confidence: 98%